Evaluation of the psychometric properties of the 18-Items dysfunctional attitudes scale (Form B) in a portuguese sample of people aged 60 and over - Silva, Celso (2024)
Abstract: The aim of the study is to assess the psychometric properties of the Portuguese version of the 18-items Dysfunctional Attitudes Scale (Form B) in a Portuguese sample of people aged 60 and over. Background: The 18-item Dysfunctional Attitudes Scale (Form B) is an instrument for assessing dysfunctional attitudes and can be useful as a predictor of depression for both initial episodes and relapses Methods: This was a one-stage cross-sectional survey of Portuguese-speaking people aged 60 years and over, able to read and write, functionally autonomous, and living in the community in their usual residences. The instrument was evaluated for its psychometric properties. Convergent validity with the Beck Depression Inventory-II was assessed. Results: The Portuguese version of the 18-item Dysfunctional Attitudes Scale (Form B) was structured into three factors, which explained a total of 58.95% of the total variance of the instrument. The exploratory factor analysis resulted in a modified model in which three factors were obtained with an eigenvalue greater than one (Kaiser’s criterion). Three factors were obtained instead of two as in the original study. It showed an internal consistency (Cronbach’s alpha = 0.770) and an interclass correlation coefficient ranging from 0.166 to 0.449, and the overall convergent validity with the Beck Depression Inventory-II was considered good; Conclusions: The Portuguese version of the Dysfunctional Attitudes Scale (DAS-18B) of people aged 60 and over demonstrated good psychometric properties.